Perlawanan Puisi Sittun ‘Aman karya Tamim al-Borghouti terhadap Rezim Zionis di Jalur Gaza - Muhammad Jafar Shiddiq; Moch. Rofiuddin (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2024)
Arabic poetry has evolved in its function over time, encompassing more than just romantic words, praise, pride, or lamentation. It now includes themes of resistance, revolutionary milestones, and struggles. This study focuses specifically on Tamim al-Borghouti's poem,